Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2174/1389203718666170918155247
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Clusterin Gene Expression

Abstract: Clusterin is a multifunctional glycoprotein whose role in cells has generated a great controversy in recent years. Since its discovery, numerous studies have linked clusterin expression deregulation with various physio-pathological processes such as cancer or Alzheimer's disease. Although the results of such investigations have sometimes been contradictory, mainly due to the dichotomous role of clusterin isoforms, it has been demonstrated that this protein is involved in diverse cellular processes, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Clusterin, encoded by the CLU gene, is an extracellular chaperone that prevents aggregation of non-native proteins. Moreover, it was demonstrated that clusterin is involved in various cellular processes, including apoptosis, cell cycle regulation, and DNA repair [23]. Overexpression of the CLU gene in six MPS types suggests that this might be a response to stress conditions caused by cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Clusterin, encoded by the CLU gene, is an extracellular chaperone that prevents aggregation of non-native proteins. Moreover, it was demonstrated that clusterin is involved in various cellular processes, including apoptosis, cell cycle regulation, and DNA repair [23]. Overexpression of the CLU gene in six MPS types suggests that this might be a response to stress conditions caused by cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 8c upregulated in stress-induced cells, such as various tumor cells and renal TEC. 32,33 In addition, CLU expression in Mφ was weak or undetectable in the immunohistochemistry of lung tissue, 34 but was upregulated in mature Mφ in human breast tumor tissues and the RAW264.7 Mφ cell line. 35 In this study, CLU proteins were detected in THP1 human monocytes, RAW264.7 Mφ and peritoneal Mφ isolated from WT mice, and their expression was upregulated in THP1 cells and RAW264.7 cells following hypoxia.…”
Section: Clu Is Associated With Decreased Polarization To M1 After LImentioning
confidence: 99%
“…Another major impediment to immunotherapy success in breast cancer patients is the selection of apoptosis-resistant cells, which constitutes one of the hallmarks of cancer [17]. Since both chemo-and immunotherapies directly or indirectly activate the cellular apoptosis machinery, tumor sensitivity to anti-cancer treatments will significantly depend on the level of expression of anti-apoptotic proteins [24] in general and, more specifically, on the existence of a pro-survival profile characterized by an increased ratio between anti-/pro-apoptotic proteins [24,90,91].…”
Section: Changes In Breast Tumor Cellsmentioning
confidence: 99%